Civil Conflict, Democratization, and Growth: Violent Democratization as Critical Juncture1. (20th February 2014) - Cervellati, Matteo; Sunde, Uwe
Abstract In this paper, we provide an empirical investigation of the interaction between violent conflicts, democratization, and growth in the "third wave" of democratization. The effect of democratization is weakened when taking into account the incidence of civil conflict. The results show that the growth effect of democratization is heterogeneous and depends on the democratization scenario. Peaceful transitions to democracy have a significant positive effect on growth that is even larger than reported previously in the literature, whereas violent transitions have no, or even negative, growth effects.